Early Career Scientists’ Guide to the Red Blood Cell – Don’t Panic! - Bogdanova, Anna; Kaestner, Lars (Frontiers in Physiology, 2020)
Why should we take interest in studying red blood cells? This mini review attempts to answer this question and highlights the problems that authors find most appealing in this dynamic research area. It addresses the early-career scientists who are just start their independent journey and facing tough times. Despite unlimited access to information, the exponential development of computational and intellectual powers, and the seemingly endless possibilities open to talented and ambitious early-career researchers, they soon realize that the pressure of immanent competition for financial support is hard. They have to hit the deadlines, produce data, publish, report, teach, manage, lead groups, and remain loving family members at the same time. Are these countless hardships worth it? We think they are! Despite centuries of research, red blood cells still form a mysterious and fascinating universe to study. These cells bring together experts within the family of the European Red Cell Society and beyond. We all share a joy for the unknown and excitement in understanding how red cells function and what they tell us about the microenvironments and macroenvironments they live in. This review is an invitation for our colleagues to join us in our quest.